Epidemiology of Reported HIV and Other Sexually Transmitted Infections During the COVID-19 Pandemic, New York City. (16th June 2021) - Braunstein, Sarah L; Slutsker, Jennifer Sanderson; Lazar, Rachael; Shah, Dipal; Hennessy, Robin R; Chen, Shirley X; Pathela, Preeti; Daskalakis, Demetre C; Schillinger, Julia A
Abstract: Early in the coronavirus disease 2019 (COVID-19) crisis, a statewide executive order (PAUSE) severely restricted the movement of New Yorkers from 23 March to 7 June 2020. We used New York City surveillance data for human immunodeficiency virus (HIV), chlamydia, gonorrhea, and syphilis to describe trends in diagnosis and reporting surrounding PAUSE. During PAUSE, the volume of positive HIV/sexually transmitted infection tests, and diagnoses of HIV, chlamydia, gonorrhea, and syphilis declined substantially, reaching a nadir in April before rebounding. Some shifts in characteristics of reported cases were identified.